Marketing Audit and Its Role in Improving the Marketing of University Products A Proposed Model - Al-Shojairy, Mohammed H. (Humanities Journal of University of Zakho, 2017)
The current research tackles the concept and applications of marketing audit in the non-profit service organizations in general and in public universities in particular, and its role in improving the marketing of university products with the aim of presenting a proposed model for the marketing audit in Iraqi public universities. Which tackles concepts, benefits, structures, and work mechanism, which contribute in activating the concept of productive university to bypass the financial crisis that confront it currently and to copy with this concept globally and support the shift in Iraqi economic system toward market economic. In this context, it has been adopted inductive descriptive approach through study and analyzes theoretical concepts of research variables and relationship between them, and describe the nature and practices of marketing audit in field of research sample. As, it has been employing the deductive approach to constructing a proposed normative model based on the results of the inductive approach as a basis for employing the concept of marketing audit in activating marketing of university products. Therefore, it has been selected the Iraqi universities a sample of the descriptive study through collect the data regards to the current reality of university marketing and marketing audit by universities websites for period between the date of establishing unit of marketing (2013) to the year (2016). It was reach several conclusions, notably the limited systems and scientific applications for university marketing. Which reflects the weak awareness of the university administration with the concept and the importance and mechanisms of effective university marketing, as well as the complete absence of the concept and applications of marketing audit and therefore the absence of his role perfectly in university marketing support. Therefore, it was recommended Current search the need to pay university administration proposed model applied and regulatory importance in the field of marketing audit to contribute to the development and university marketing real, effective and efficient.